2007
DOI: 10.1002/hep.21797
|View full text |Cite
|
Sign up to set email alerts
|

Innate immune response to double-stranded RNA in biliary epithelial cells is associated with the pathogenesis of biliary atresia

Abstract: B iliary atresia (BA) is characterized by a progressive, inflammatory, and sclerosing cholangiopathy. Little is known about the etiology and pathogenesis of BA, but recent studies have demonstrated the presence of Reoviridae (type 3 reovirus and type C rotavirus) having a double-strand RNA (dsRNA) in liver tissue of patients with BA, although conflicting results have been reported. [1][2][3][4][5] Moreover, the infection of newborn Balb/cmice with Reoviridae including type A rhesus rotavirus and type 3 reoviru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
101
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(104 citation statements)
references
References 32 publications
2
101
1
Order By: Relevance
“…NF-κB is a key molecule in the expression of various inflammatory genes and IRF3 is an important transcriptional factor in antiviral innate immune reactions. Both of NF-κB and IRF3 are thought to be implicated in the pathogenesis of BA (3,4). In RNA interference experiments, we found that both of NF-κB p65 and IRF3 are involved in CCL5 expression in HuCCT1 cells treated with poly IC.…”
Section: Poly Ic Induces the Expression Of Ccl5 In Hucct1 Human Bile mentioning
confidence: 77%
See 2 more Smart Citations
“…NF-κB is a key molecule in the expression of various inflammatory genes and IRF3 is an important transcriptional factor in antiviral innate immune reactions. Both of NF-κB and IRF3 are thought to be implicated in the pathogenesis of BA (3,4). In RNA interference experiments, we found that both of NF-κB p65 and IRF3 are involved in CCL5 expression in HuCCT1 cells treated with poly IC.…”
Section: Poly Ic Induces the Expression Of Ccl5 In Hucct1 Human Bile mentioning
confidence: 77%
“…Toll-like receptors (TLRs) are members of pattern recognition receptors, and TLR3 is a receptor for dsRNA. TLR3 is expressed in biliary epithelial cells and is involved in biliary innate immune reactions (4). It is well known that activation of TLR3 signaling induces the expression of various cytokines and chemokines.…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 To understand the pathogenesis of the disease and improve the outcome of BA patients, research has focused on the inflammatory process in liver and bile ducts, in which several factors are remarkably elevated, such as activated CD4 and CD8 T-cells, TNF alpha, IFNg and other proinflammatory T H 1 cytokines (3)(4)(5)(6)(7)(8). By the time of diagnosis, however, the disease has already reached an advanced state, characterized by the complete obstruction of the extrahepatic bile ducts with impaired bile flow and fibrosis or cirrhosis of the liver.…”
Section: Introductionmentioning
confidence: 99%
“…19,22,23 Shivakumar et al 24 described the presence of natural killer cells in the vicinity of intrahepatic bile ducts with accompanying overexpression of genes involved in cytotoxicity, while Harada et al 131 have suggested a role for Toll-like receptor (TLR)-related injury in biliary atresia by demonstrating continued upregulation of molecules involved in biliary injury and apoptosis after exposure of cultured biliary epithelial cells to synthetic double-stranded viral RNA analogue. These findings suggest that innate immune responses may play a role in the pathogenesis of biliary atresia.…”
Section: Immunologic Injurymentioning
confidence: 99%